Uniportal video-assisted thoracic surgery right upper lobectomy with systemic lymphadenectomy - Han, Ding-Pei; Xiang, Jie; Li, He-Cheng; Hang, Jun-Biao (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
This video demonstrated a performance of uniportal video-assisted thoracoscopic surgery (VATS) right upper lobectomy with systemic lymphadenectomy. The patient had a malignant mass in his right upper lobe. The operator took a posterior to anterior approach to dissection the right upper lobe, the adjacent structures were clearly demonstrated after the entire dissection of mediastinal lymph nodes. Postoperative pathological report suggested the stage of the tumor was T1bN0M0 (stage IA).